Accessing the Long‐Lived Triplet Excited States in Transition‐Metal Complexes: Molecular Design Rationales and Applications. Issue 1 (30th November 2015) - Cui, Xiaoneng; Zhao, Jianzhang; Mohmood, Zafar; Zhang, Caishun
Abstract: Transition‐metal complex triplet photosensitizers are versatile compounds that have been widely used in photocatalysis, photovoltaics, photodynamic therapy (PDT) and triplet–triplet annihilation (TTA) upconversion. The principal photophysical processes in these applications are the intermolecular energy transfer or electron transfer. One of the major challenges facing these triplet photosensitizers is the short triplet‐state lifetime, which is detrimental to the above‐mentioned photophysical processes. In order to address this challenge, transition‐metal complexes showing long‐lived triplet excited states are highly desired. This review article summarizes the development of this fascinating area, including the molecular design rationales, the principal photophysical properties, and the applications of these complexes in PDT and TTA upconversion. Abstract : Transition‐metal complexes with long‐lived triplet excited states have a variety of applications in photocatalysis, photovoltaics, photodynamic therapy, and triplet–triplet annihilation upconversion. The development of this area, including the photophysical considerations, molecular design rationales, and applications, is summarized herein.